(untitled) (TAJ: Journal of Teachers Association, 2021)
Nipah virus, a zoonotic paramyxovirus transmitted by specific types of fruit bats, causes an occasional outbreak of encephalitis in Bangladesh and India. We are reporting two cases of Nipah encephalitis with distinct MRI findings. TAJ 2021; 34: No-1: 106-108